Tinjauan Kriminologi Terhadap Tindak Pidana Persetubuhan Oleh Ayah Tiri Terhadap Anak Korban Di Wilayah Hukum Kepolisian Resor Kupang Kota - Alzuhri, Firda Khairinisa; Manuain, Orpa G; Kian, Darius A (Artemis Law Journal, 2023)
Indonesia is a state based on law, which means that all actions and patterns of behavior of every citizen must be in accordance with the norms and provisions regulated by the state. One form of crime that is very detrimental and disturbing to society is the crime of sexual intercourse of child victims. In the last 4 years there have been 17 cases of criminal acts of child victimization committed by the closest person in the jurisdiction of the Kupang City Resort Police and among them were committed by stepfathers. The main problems in this thesis are: (1) What are the factors causing the criminal offense of intercourse by stepfather against children in the jurisdiction of Kupang City Police Resort? (2) How are the efforts to overcome the criminal offense of intercourse by stepfather against children in the jurisdiction of Kupang City Police Resort? This research is a study that uses criminological studies that discuss the science that studies the causes of crime, the concepts used to explain why crime occurs. (1) the factors causing the crime of intercourse by stepfather against children are external factors and internal factors. (2) efforts to overcome the criminal offense of intercourse by stepfather against children are pre-emtif efforts, preventive efforts and repressive efforts. Based on the results of this study, it can be seen: the factors causing the crime of sexual intercourse by a stepfather against a child victim with Decision No. 200/Pid.Sus/2021PN kpg in 2021 are the psychological condition of the perpetrator who cannot control his sexual appetite properly and the condition of the perpetrator's biological needs for sex that are not fulfilled. Misuse of technology, the environment and alcoholic beverages, Countermeasures carried out by the Police in overcoming cases of criminal acts of intercourse committed by stepfathers against child victims include Pre-emtif efforts are carried out by the community development function (Binmas), Preventive efforts: to reduce the risks and push factors for the criminal act of intercourse, , Repressive efforts are the actions of law enforcement officials that are carried out actively so that the crimes that are occurring can be followed up by the authorities with strict law enforcement for the perpetrators.